Expression of angiotensin II receptors in the caprine ovary and improvement of follicular viability in vitro. Issue 4 (14th October 2015) - Bruno, J.B.; Lima-Verde, I.B.; Celestino, J.J.H.; Lima, L.F.; Matos, M.H.T.; Faustino, L.R.; Donato, M.A.M.; Peixoto, C.A.; Campello, C.C.; Silva, J.R.V.; Figueiredo, J.R.
Summary: This study aimed to evaluate mRNA levels of angiotensin II (ANG II) receptors (AGTR1 and AGTR2) in caprine follicles and to investigate the influence of ANG II on the viability and in vitro growth of preantral follicles. Real-time polymerase chain reaction (PCR) was used to quantify AGTR1 and AGTR2 mRNA levels in the different follicular stages. For culture, caprine ovaries were collected, cut into 13 fragments and then either directly fixed for histological and ultrastructural analysis (fresh control) or placed in culture for 1 or 7 days in α-minumum essential medium plus (α-MEM + ) with 0, 1, 5, 10, 50 or 100 ng/ml ANG II. Then, the fragments were destined to morphological, viability and ultrastructural analysis. The results showed that primordial follicles had higher levels of AGTR1 and AGTR2 mRNA than secondary follicles. Granulosa/theca cells from antral follicles had higher levels of AGTR1 mRNA than their respective cumulus–oocyte complex (COCs). After 7 days of culture, ANG II (10 or 50 ng/ml) maintained the percentages of normal follicles compared with α-MEM + . Fluorescence and ultrastructural microscopy confirmed follicular integrity in ANG II (10 ng/ml). In conclusion, a high expression of AGTR1 and AGTR2 is observed in primordial follicles. Granulosa/theca cells from antral follicles had higher levels of AGTR1 mRNA. Finally, 10 ng/ml ANG II maintained the viability of caprine preantral follicles after in vitro culture.